Program Peduli Memutus Rantai Penyebaran Virus Covid-19 Melalui Kegiatan Pembagian Masker Non Medis Untuk Pekerja Informal Di Kota Ternate - Hery Purnomo; M. Amrin MS. Conoras; Endah Harisun (Journal Of Khairun Community Services, 2021)
In accordance with the advice from the WHO and the Task Force for the Acceleration of Handling Covid-19, everyone is required to wear a mask every time they are outside the room or in the home environment. As an effort to break the chain of transmission of the Covid-19 virus in North Maluku in general and the City of Ternate in particular. The Faculty of Engineering, Khairun University, through the 2020 Faculty of Engineering Community Service activities, carried out mask distribution activities to people who often did activities outside the home and informal workers. This Community Service activity was carried out in the Jati Village and the targets of this service were the congregation of the Nurul Insan Mosque and informal workers in the Jati Village. The approach method used is to be directly involved in the distribution of masks and in collaboration with Khairun University KUBERMAS students who work in Jati Village. The distribution of these masks is a preventive measure to protect and educate residents from Covid-19. Moreover, the health protocol also obliges the public to wear masks when doing activities outside the home. The distribution of cloth masks to the public is also aimed at educating them. With the hope, people can make their own masks made from cloth